A Quadratic Relation in the Bernoulli Numbers - Beals-Reid, Madeline (The PUMP Journal of Undergraduate Research, 2023)
We present a proof of an identity involving the Bernoulli numbers. This identity has been proved, over the centuries, by many different methods. Our method uses a technique from over a millennium ago for finding polynomial expressions for sums of powers of integers.